К вопросу о нетипических значениях русских глаголов движенияи их армянских эквивалентах - Испирян, Мариам (Զանգակ հրատ.)
Հոդվածում դիտարկվում են ռուսաց լեզվի շարժում արտահայտող բայերի տարբերակված առանձնահատկությունները, ուղղվածությունը /շարժման տարածական կողմնորոշում/, հակիրճությունը /շարժման ոչ ընդհատությունը/, շարժման ձևը: The paper embraces differential features of motion verbs in Russian. The semantic structure of verbs of movement comprises at least three distinguishing characteristics: direction / spatial orientation of movement, multiplicity / non–multiplicity of movement; means of motion.
Keywords: Методика обучения и преподавания